Air filter material and preparation method thereof
Through the combination of modified nanomanganese dioxide and polyacrylonitrile and electrospinning technology, a multifunctional air filter material is formed, which solves the problems of large resistance pressure drop and insufficient removal ability of the nanofiber filter membrane, and achieves high-efficiency filtration, antibacterial and resistance The combustion and formaldehyde removal effect is reduced and the pressure drop is reduced.
Patent Information
- Application Number
- CN202411380861.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The resistance pressure drop of existing nanofiber filter membranes is large and easy to block. The simple removal of fine particulate matter in polluted air cannot meet the practical application needs of multifunctional air filter materials.
Modified manganese dioxide is prepared by reacting the silicone quaternary ammonium salt with nanomanganese dioxide, and the polyacrylonitrile is subjected to carboxy, hydrophilic and quaternary ammonium modification treatment, combined with electrospinning technology to form hydrophilic-hydrophobic - Superhydrophobic structure of air filter material, load-modified nanomanganese dioxide to improve dust removal and catalytic performance.
It achieves efficient filtration performance, antibacterial, flame retardant and formaldehyde removal effects, while reducing pressure drop, extending service life, and improving the mechanical properties and self-cleaning ability of the material.
Smart Images

Figure SMS_3 
Figure SMS_5 
Figure SMS_7
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, in particular to an air filter material and a preparation method thereof. Background Art
[0002] Studies have found that air pollutants can reduce people's immune system and increase the risk of various chronic diseases, especially fine particles such as PM 2.5 , has a larger specific surface area, stays in the air longer, and is easy to adsorb harmful pollutants, accelerating the spread of harmful microorganisms, posing a greater threat to human health.
[0003] Nanofibers have the advantages of nanometer-scale fiber diameter, large specific surface area, high porosity, light weight, good connectivity, etc., and have great application potential in air filtration. However, the small diameter and large bulk density of nanofiber filter membranes make their resistance pressure drop larger, which blocks the filter pores of the nanofiber filter membrane and shortens the use time, which limits the application of nanofiber filter membranes to a certain extent. In addition to solid particles, polluted air may also contain microorganisms, formaldehyde and other substances that seriously endanger human health. Therefore, simply removing fine particles in polluted air can no longer meet the actual application requirements of air filtration materials, and people have put forward higher requirements for the multifunctionality of protective equipment. In recent years, on the basis of the particle removal function, giving air filtration materials certain functionality, such as antibacterial and removal of harmful gases, has become a hot topic in the research field of new air filtration materials. Summary of the invention
[0004] The object of the present invention is to provide an air filter material and a preparation method thereof to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The invention discloses an air filter material. The air filter material comprises the following steps: firstly reacting organosilicon quaternary ammonium salt with nano manganese dioxide to obtain modified nano manganese dioxide; reacting polyacrylonitrile with sodium hydroxide solution to obtain carboxyl modified polyacrylonitrile; reacting carboxyl modified polyacrylonitrile with glycidol and ethylenediaminetetramethylenephosphonic acid to obtain hydrophilic modified polyacrylonitrile; reacting carboxyl modified polyacrylonitrile with epichlorohydrin and octadecyldimethyl tertiary amine to obtain quaternary ammonium modified polyacrylonitrile; preparing spinning solution with hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile and polyacrylonitrile and electrostatic spinning; and finally loading a layer with modified nano manganese dioxide to obtain the air filter material.
[0007] As an optimization, the organosilicon quaternary ammonium salt is prepared by reacting 3-chloropropylmethyldimethoxysilane with hexadecyldimethyl tertiary amine.
[0008] As an optimization, the weight average molecular weight of the polyacrylonitrile is 149,000-150,000.
[0009] As an optimization, the electrospinning is firstly spun with a hydrophilic modified polyacrylonitrile spinning solution, then spun with a quaternary ammonium modified polyacrylonitrile spinning solution, and finally spun with a polyacrylonitrile spinning solution.
[0010] As an optimization, the loading of the modified nano manganese dioxide is carried out using nano atomization technology.
[0011] As an optimization, the nano manganese dioxide model is JR-MnO2-50, with a particle size of 50 nm, purchased from Xuancheng Jingrui New Materials Co., Ltd.
[0012] A method for preparing an air filter material comprises the following steps:
[0013] (1) 3-chloropropylmethyldimethoxysilane, hexadecyldimethyl tertiary amine, sodium iodide and anhydrous ethanol were mixed uniformly in a molar ratio of 1.1:1:0.01:21, stirred and refluxed at 80-85°C and 300-500 r / min for 38-42 hours under a nitrogen atmosphere, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure, washed with ethanol for 3-5 times, and vacuum dried at 50-60°C for 6-8 hours to obtain an organosilicon quaternary ammonium salt;
[0014] (2) Mix nano manganese dioxide and anhydrous ethanol in a mass ratio of 1:(40-45), disperse them evenly under ultrasonication at room temperature for 20-30 min, stir them at 300-400 r / min for 2-3 h, add quaternary ammonium salt of organosilicon twice the mass of nano manganese dioxide, reflux at 80-85°C and 300-400 r / min for 16-18 h, centrifuge at 8000-10000 r / min for 10-15 min after the reaction is completed, wash them with ethanol for 4-6 times, and vacuum dry them at 50-60°C for 6-8 h to obtain modified nano manganese dioxide;
[0015] (3) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:(15-25), reacted at 65-75°C and 200-300 r / min for 2-3 hours, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 50-60°C for 7-8 hours to obtain carboxyl-modified polyacrylonitrile;
[0016] (4) Carboxyl modified polyacrylonitrile, glycidol and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(0.4-0.5):(20-30), reacted in a microwave reactor at 70-75°C and 300-400 r / min for 1.5-2 h, added ethylenediaminetetramethylenephosphonic acid in an amount equal to that of glycidol, reacted in a microwave reactor at 70-75°C and 300-400 r / min for 2-2.5 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 3-5 times, then washed with pure water 3-5 times, and vacuum dried at 60-70°C for 8-10 h to obtain hydrophilic modified polyacrylonitrile;
[0017] (5) Carboxyl modified polyacrylonitrile, epichlorohydrin and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(0.5-0.6):(25-35), reacted in a microwave reactor at 70-75°C and 300-500 r / min for 1-1.5 h, nitrogen was introduced, octadecyl dimethyl tertiary amine of the same mass as epichlorohydrin was added, potassium iodide of 0.02 times the mass of epichlorohydrin was added, reacted in a microwave reactor at 80-85°C and 350-450 r / min for 6-8 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 3-5 times, then washed with pure water 3-5 times, and vacuum dried at 60-70°C for 8-10 h to obtain quaternary ammonium modified polyacrylonitrile;
[0018] (6) Dissolve hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile, and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution, 10 wt% quaternary ammonium modified polyacrylonitrile spinning solution, and 10 wt% polyacrylonitrile spinning solution, respectively; ultrasonically disperse modified nano manganese dioxide in anhydrous ethanol to prepare 2 wt% modified nano manganese dioxide dispersion; inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a propulsion speed of 0.7 ml / h, a voltage of 25-27 kV, a distance between the needle tip and the collecting drum of 20 cm, and cover the collecting drum with 400 mesh The metal mesh was spun at 23-27°C and 46%-54%RH for 38-44min, then replaced with quaternary ammonium modified polyacrylonitrile spinning solution at a propulsion speed of 0.6ml / h and a voltage of 22-25kV for 19-22min, then replaced with polyacrylonitrile spinning solution at a propulsion speed of 0.5ml / h and a voltage of 15-18kV. An atomizer containing modified nano-manganese dioxide dispersion was placed on the collecting drum with the spray direction of the atomizer being orthogonal to the collecting drum. The material was spun for 19-22min, dried in vacuum at 50-60°C for 6-8h, and peeled off from the collecting drum to obtain an air filter material.
[0019] As an optimization, the reaction process of the organosilicon quaternary ammonium salt in step (1) is as follows:
[0020] .
[0021] As an optimization, the reaction process of carboxyl-modified polyacrylonitrile in step (3) is as follows:
[0022] .
[0023] As an optimization, the hydrophilic modified polyacrylonitrile reaction process in step (4) is as follows:
[0024]
[0025] .
[0026] As an optimization, the reaction process of quaternary ammonium modified polyacrylonitrile in step (5) is as follows:
[0027]
[0028] .
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] When preparing the air filter material, the invention firstly reacts 3-chloropropylmethyldimethoxysilane with hexadecyldimethyl tertiary amine to obtain organosilicon quaternary ammonium salt; reacts the organosilicon quaternary ammonium salt with nano manganese dioxide to obtain modified nano manganese dioxide; reacts polyacrylonitrile with sodium hydroxide solution to obtain carboxyl modified polyacrylonitrile; reacts carboxyl modified polyacrylonitrile with glycidol and ethylenediaminetetramethylenephosphonic acid to obtain hydrophilic modified polyacrylonitrile; reacts carboxyl modified polyacrylonitrile with epichlorohydrin and octadecyldimethyl tertiary amine to obtain quaternary ammonium modified polyacrylonitrile; prepares the hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile and polyacrylonitrile into spinning solution and electrostatic spinning, and finally loads the modified nano manganese dioxide on a layer to obtain the air filter material.
[0031] First, nano manganese dioxide is reacted with organosilicon quaternary ammonium salt to obtain modified nano manganese dioxide. The methoxy group on the organosilicon quaternary ammonium salt combines with the hydroxyl group on the surface of nano manganese dioxide. The long carbon chain on the silane makes the nano manganese dioxide more compatible with the polyacrylonitrile body, avoiding agglomeration and making the subsequent loading more uniform.
[0032] Secondly, polyacrylonitrile is treated with sodium hydroxide solution to obtain carboxyl-modified polyacrylonitrile, so that it has hydrophilic carboxyl groups and leaves reactive groups for subsequent modification; the carboxyl-modified polyacrylonitrile is first subjected to an esterification reaction with propylene oxide, and then ethylenediaminetetramethylenephosphonic acid is subjected to an esterification reaction with hydroxyl groups left by the ring-opening of the epoxy groups to obtain hydrophilic modified polyacrylonitrile, and the hydrophilic ethylenediaminetetramethylenephosphonic acid is connected to the main chain by bonding, and the phosphorus and nitrogen elements in the ethylenediaminetetramethylenephosphonic acid can provide a synergistic flame retardant effect and improve its flame retardant properties, and the ethylenediaminetetramethylenephosphonic acid has a negative charge and can better provide an electrostatic adsorption dust removal effect and improve the dust removal performance of the air filter material.
[0033] Again, the carboxyl-modified polyacrylonitrile is first reacted with epichlorohydrin, and the carboxyl group and the epoxy group undergo a ring-opening esterification reaction, while a reactive halogenated group is introduced. Then, under the catalysis of sodium iodide, a quaternization reaction occurs with octadecyl dimethyl tertiary amine to obtain quaternary ammonium-modified polyacrylonitrile. The long carbon chain of the tertiary amine makes the surface of the quaternary ammonium-modified polyacrylonitrile hydrophobic, and the long carbon chain quaternary ammonium group brings good antibacterial effect. The quaternary ammonium group carries a positive charge, which not only improves the dust removal effect, but also can undergo electrostatic bonding with the hydrophilic modified polyacrylonitrile layer, thereby improving the mechanical properties.
[0034] Finally, the hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile and polyacrylonitrile are prepared into spinning solution and electrostatically spun. The last layer is loaded with modified nano manganese dioxide to obtain air filter material. The hydrophilic modified polyacrylonitrile of the first layer and the quaternary ammonium modified polyacrylonitrile of the second layer are negatively charged and positively charged respectively, which can be electrostatically combined to improve the breaking strength and can electrostatically adsorb most of the charged dust in the air. The third layer of polyacrylonitrile is loaded with modified nano manganese dioxide by nano spray technology during spinning. The long carbon chain of the surface modification of nano manganese dioxide improves the compatibility and is combined with the nano atomization technology to make the modified nano manganese dioxide loading more uniform. At the same time, it can also form a super hydrophobic structure with polyacrylonitrile and has the potential for self-cleaning. The loading of nano manganese dioxide can catalyze the decomposition of harmful gases such as formaldehyde in the air, and the surface of nano manganese dioxide The surface-modified long carbon chain of quaternary ammonium can improve the adsorption of such organic volatile gases, and the quaternary ammonium group also has an antibacterial effect, which works simultaneously with the quaternary ammonium-modified polyacrylonitrile of the second layer; before electrospinning, the surface of the collecting drum is covered with a 400-mesh metal mesh, which can attract the charged droplets in a high-voltage electric field in a directional manner, so that the first layer has an orderly arrangement and a smaller pore size, and as the spinning proceeds, its control over the direction of movement of the spinning solution weakens, gradually forming a disordered structure, and as the spinning thickness increases, the pore size gradually increases, forming a multi-level structure, which has high-efficiency filtration performance while reducing the pressure drop; the hydrophilic-hydrophobic-superhydrophobic structure can make the water droplets gathered on the superhydrophobic layer gradually transferred to the hydrophilic layer through capillary action, realize the directional transmission of water molecules, and keep the superhydrophobic layer dry. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] A method for preparing an air filter material, the method comprising the following steps:
[0038] (1) 3-Chloropropylmethyldimethoxysilane, hexadecyldimethyl tertiary amine, sodium iodide and anhydrous ethanol were mixed uniformly in a molar ratio of 1.1:1:0.01:21, stirred and refluxed at 80°C and 300 r / min for 42 h under a nitrogen atmosphere, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure, washed with ethanol three times, and vacuum dried at 50°C for 8 h to obtain an organosilicon quaternary ammonium salt;
[0039] (2) Nano manganese dioxide and anhydrous ethanol were mixed in a mass ratio of 1:40, ultrasonically dispersed at room temperature for 20 minutes, stirred at 300 r / min for 3 hours, added with organosilicon quaternary ammonium salt twice the mass of nano manganese dioxide, refluxed at 80°C and 300 r / min for 18 hours, centrifuged at 8000 r / min for 15 minutes after the reaction was completed, washed with ethanol for 4 times, and vacuum dried at 50°C for 8 hours to obtain modified nano manganese dioxide;
[0040] (3) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:15, reacted at 65°C and 200 r / min for 3 h, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 50°C for 8 h to obtain carboxyl-modified polyacrylonitrile;
[0041] (4) Carboxyl modified polyacrylonitrile, glycidol and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.4:20, reacted in a microwave reactor at 70°C and 300 r / min for 2 h, ethylenediaminetetramethylenephosphonic acid in an amount equal to that of glycidol was added, reacted in a microwave reactor at 70°C and 300 r / min for 2.5 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed 3 times with ethanol, then washed 3 times with pure water, and vacuum dried at 60°C for 10 h to obtain hydrophilic modified polyacrylonitrile;
[0042] (5) Carboxyl-modified polyacrylonitrile, epichlorohydrin, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.5:25, reacted in a microwave reactor at 70°C and 300 r / min for 1.5 h, nitrogen was introduced, octadecyl dimethyl tertiary amine of the same mass as epichlorohydrin was added, potassium iodide of 0.02 times the mass of epichlorohydrin was added, reacted in a microwave reactor at 80°C and 350 r / min for 8 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed 3 times with ethanol, then washed 3 times with pure water, and vacuum dried at 60°C for 10 h to obtain quaternary ammonium-modified polyacrylonitrile;
[0043] (6) Dissolve hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile, and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution, 10 wt% quaternary ammonium modified polyacrylonitrile spinning solution, and 10 wt% polyacrylonitrile spinning solution, respectively; ultrasonically disperse modified nano manganese dioxide in anhydrous ethanol to prepare 2 wt% modified nano manganese dioxide dispersion; inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a propulsion speed of 0.7 ml / h, a voltage of 25 kV, and a distance between the needle tip and the collecting drum of 20 cm. The collecting drum was covered with a 400-mesh metal wire mesh, and the spinning was carried out at 23°C, 46%RH for 38 min. The spinning solution was replaced with quaternary ammonium modified polyacrylonitrile spinning solution, the propulsion speed was 0.6 ml / h, the voltage was 22 kV, and the spinning was carried out for 19 min. The spinning solution was replaced with polyacrylonitrile spinning solution, the propulsion speed was 0.5 ml / h, the voltage was 15 kV, and an atomizer containing modified nano-manganese dioxide dispersion was placed on the collecting drum with the atomizer spraying direction orthogonal to the collecting drum. The spinning was carried out for 19 min, and the air filter material was vacuum dried at 50°C for 8 h and peeled off from the collecting drum to obtain the air filter material.
[0044] Example 2
[0045] A method for preparing an air filter material, the method comprising the following steps:
[0046] (1) 3-Chloropropylmethyldimethoxysilane, hexadecyldimethyl tertiary amine, sodium iodide and anhydrous ethanol were mixed uniformly in a molar ratio of 1.1:1:0.01:21, stirred and refluxed at 80°C and 400 r / min for 40 h under a nitrogen atmosphere, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure, washed with ethanol for 4 times, and vacuum dried at 55°C for 7 h to obtain an organosilicon quaternary ammonium salt;
[0047] (2) Mix nano manganese dioxide and anhydrous ethanol in a mass ratio of 1:42, disperse them uniformly under ultrasonication at room temperature for 25 min, stir them at 350 r / min for 2.5 h, add organosilicon quaternary ammonium salt twice the mass of nano manganese dioxide, reflux at 85°C and 350 r / min for 17 h, centrifuge at 9000 r / min for 10 min after the reaction is completed, wash them with ethanol for 5 times, and vacuum dry them at 55°C for 7 h to obtain modified nano manganese dioxide;
[0048] (3) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:20, reacted at 70°C and 250 r / min for 2.5 h, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 55°C for 8 h to obtain carboxyl-modified polyacrylonitrile;
[0049] (4) Carboxyl modified polyacrylonitrile, glycidol and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.45:25, reacted in a microwave reactor at 75°C and 350 r / min for 1.5 h, ethylenediaminetetramethylenephosphonic acid in an amount equal to that of glycidol was added, reacted in a microwave reactor at 75°C and 350 r / min for 2 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 4 times, then washed with pure water 4 times, and vacuum dried at 65°C for 9 h to obtain hydrophilic modified polyacrylonitrile;
[0050] (5) Carboxyl-modified polyacrylonitrile, epichlorohydrin, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.55:30, reacted in a microwave reactor at 75°C and 400 r / min for 1 h, nitrogen was introduced, octadecyl dimethyl tertiary amine of the same mass as epichlorohydrin was added, potassium iodide of 0.02 times the mass of epichlorohydrin was added, reacted in a microwave reactor at 85°C and 400 r / min for 7 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed 4 times with ethanol, and then washed 4 times with pure water, and vacuum dried at 65°C for 7 h to obtain quaternary ammonium-modified polyacrylonitrile;
[0051] (6) Dissolve hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile, and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution, 10 wt% quaternary ammonium modified polyacrylonitrile spinning solution, and 10 wt% polyacrylonitrile spinning solution, respectively; ultrasonically disperse modified nano manganese dioxide in anhydrous ethanol to prepare 2 wt% modified nano manganese dioxide dispersion; inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a propulsion speed of 0.7 ml / h, a voltage of 26 kV, and a distance between the needle tip and the collecting drum of 20 cm; The collecting drum was covered with a 400-mesh metal wire mesh, and the spinning was carried out at 25°C, 50% RH for 40 min. The spinning solution was replaced with quaternary ammonium modified polyacrylonitrile spinning solution, the propulsion speed was 0.6 ml / h, the voltage was 23 kV, and the spinning was carried out for 20 min. The spinning solution was replaced with polyacrylonitrile spinning solution, the propulsion speed was 0.5 ml / h, and the voltage was 16 kV. An atomizer containing modified nano-manganese dioxide dispersion was placed on the collecting drum with the spray direction of the atomizer being orthogonal to the collecting drum. The spinning was carried out for 20 min, and the air filter material was vacuum dried at 55°C for 7 h and peeled off from the collecting drum to obtain an air filter material.
[0052] Example 3
[0053] A method for preparing an air filter material, the method comprising the following steps:
[0054] (1) 3-Chloropropylmethyldimethoxysilane, hexadecyldimethyl tertiary amine, sodium iodide and anhydrous ethanol were mixed uniformly in a molar ratio of 1.1:1:0.01:21, stirred and refluxed at 85°C and 500 r / min for 42 h under a nitrogen atmosphere, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure, washed with ethanol 5 times, and vacuum dried at 60°C for 6 h to obtain an organosilicon quaternary ammonium salt;
[0055] (2) Nano manganese dioxide and anhydrous ethanol were mixed in a mass ratio of 1:45, ultrasonically dispersed at room temperature for 30 minutes, stirred at 400 r / min for 3 hours, added with organosilicon quaternary ammonium salt twice the mass of nano manganese dioxide, refluxed at 85°C and 400 r / min for 16 hours, centrifuged at 10000 r / min for 10 minutes after the reaction was completed, washed with ethanol for 6 times, and vacuum dried at 60°C for 6 hours to obtain modified nano manganese dioxide;
[0056] (3) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:25, reacted at 75°C and 300 r / min for 2 h, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 60°C for 8 h to obtain carboxyl-modified polyacrylonitrile;
[0057] (4) Carboxyl modified polyacrylonitrile, glycidol and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.5:30, reacted in a microwave reactor at 75°C and 400 r / min for 1.5 h, ethylenediaminetetramethylenephosphonic acid in an amount equal to that of glycidol was added, reacted in a microwave reactor at 75°C and 400 r / min for 2 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 5 times, then washed with pure water 5 times, and vacuum dried at 70°C for 8 h to obtain hydrophilic modified polyacrylonitrile;
[0058] (5) Carboxyl-modified polyacrylonitrile, epichlorohydrin, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.6:35, reacted in a microwave reactor at 75°C and 500 r / min for 1 h, nitrogen was introduced, octadecyl dimethyl tertiary amine of the same mass as epichlorohydrin was added, potassium iodide of 0.02 times the mass of epichlorohydrin was added, reacted in a microwave reactor at 85°C and 450 r / min for 6 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 5 times, then washed with pure water 5 times, and vacuum dried at 70°C for 8 h to obtain quaternary ammonium-modified polyacrylonitrile;
[0059] (6) Dissolve hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile, and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution, 10 wt% quaternary ammonium modified polyacrylonitrile spinning solution, and 10 wt% polyacrylonitrile spinning solution, respectively; ultrasonically disperse modified nano manganese dioxide in anhydrous ethanol to prepare 2 wt% modified nano manganese dioxide dispersion; inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a propulsion speed of 0.7 ml / h, a voltage of 27 kV, and a distance between the needle tip and the collecting drum of 20 cm. The collecting drum was covered with a 400-mesh metal wire mesh, and the spinning was carried out at 27°C and 54%RH for 44 min. The spinning solution was changed to quaternary ammonium modified polyacrylonitrile spinning solution, the propulsion speed was 0.6 ml / h, the voltage was 25 kV, and the spinning was carried out for 22 min. The spinning solution was changed to polyacrylonitrile spinning solution, the propulsion speed was 0.5 ml / h, the voltage was 18 kV, and an atomizer containing modified nano-manganese dioxide dispersion was placed on the collecting drum with the atomizer spraying direction orthogonal to the collecting drum. The spinning was carried out for 22 min, and the air filter material was vacuum dried at 60°C for 8 h and peeled off from the collecting drum to obtain the air filter material.
[0060] Comparative Example 1
[0061] A method for preparing an air filter material, the method comprising the following steps:
[0062] (1) Nano manganese dioxide and anhydrous ethanol were mixed in a mass ratio of 1:42, ultrasonically dispersed at room temperature for 25 minutes, stirred at 350 r / min for 2.5 hours, methyltriethoxysilane twice the mass of nano manganese dioxide was added, refluxed at 85°C and 350 r / min for 17 hours, centrifuged at 9000 r / min for 10 minutes after the reaction was completed, washed with ethanol for 5 times, and vacuum dried at 55°C for 7 hours to obtain modified nano manganese dioxide;
[0063] (2) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:20, reacted at 70°C and 250 r / min for 2.5 h, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 55°C for 8 h to obtain carboxyl-modified polyacrylonitrile;
[0064] (3) Carboxyl modified polyacrylonitrile, glycidol and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.45:25, reacted in a microwave reactor at 75°C and 350 r / min for 1.5 h, ethylenediaminetetramethylenephosphonic acid in an amount equal to that of glycidol was added, reacted in a microwave reactor at 75°C and 350 r / min for 2 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed 4 times with ethanol, then washed 4 times with pure water, and vacuum dried at 65°C for 9 h to obtain hydrophilic modified polyacrylonitrile;
[0065] (4) Dissolve the hydrophilic modified polyacrylonitrile and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution and 10 wt% polyacrylonitrile spinning solution, ultrasonically disperse the modified nano manganese dioxide in anhydrous ethanol to prepare a 2 wt% modified nano manganese dioxide dispersion, and inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a propulsion speed of 0.7 ml / h, a voltage of 26 kV, and a distance between the needle tip and the collecting roller of 20 cm, cover the collecting drum with a 400-mesh metal wire mesh, spin for 40 min at 25°C, 50% RH, replace with polyacrylonitrile spinning solution, advance speed of 0.5 ml / h, voltage of 16 kV, spin for 20 min first, place an atomizer filled with modified nano manganese dioxide dispersion on the collecting drum, with the atomizer spray direction orthogonal to the collecting drum, spin for another 20 min, dry in vacuum at 55°C for 7 h, peel off from the collecting drum, and obtain an air filter material.
[0066] Comparative Example 2
[0067] A method for preparing an air filter material, the method comprising the following steps:
[0068] (1) 3-Chloropropylmethyldimethoxysilane, hexadecyldimethyl tertiary amine, sodium iodide and anhydrous ethanol were mixed uniformly in a molar ratio of 1.1:1:0.01:21, stirred and refluxed at 80°C and 400 r / min for 40 h under a nitrogen atmosphere, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure, washed with ethanol for 4 times, and vacuum dried at 55°C for 7 h to obtain an organosilicon quaternary ammonium salt;
[0069] (2) Mix nano manganese dioxide and anhydrous ethanol in a mass ratio of 1:42, disperse them uniformly under ultrasonication at room temperature for 25 min, stir them at 350 r / min for 2.5 h, add organosilicon quaternary ammonium salt twice the mass of nano manganese dioxide, reflux at 85°C and 350 r / min for 17 h, centrifuge at 9000 r / min for 10 min after the reaction is completed, wash them with ethanol for 5 times, and vacuum dry them at 55°C for 7 h to obtain modified nano manganese dioxide;
[0070] (3) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:20, reacted at 70°C and 250 r / min for 2.5 h, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 55°C for 8 h to obtain carboxyl-modified polyacrylonitrile;
[0071] (4) Carboxyl modified polyacrylonitrile, propylene oxide, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.45:25, reacted in a microwave reactor at 75°C and 350 r / min for 1.5 h, naturally cooled to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 4 times, then washed with pure water 4 times, and vacuum dried at 65°C for 9 h to obtain hydrophilic modified polyacrylonitrile;
[0072] (5) Carboxyl-modified polyacrylonitrile, epichlorohydrin, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.55:30, reacted in a microwave reactor at 75°C and 400 r / min for 1 h, nitrogen was introduced, octadecyl dimethyl tertiary amine of the same mass as epichlorohydrin was added, potassium iodide of 0.02 times the mass of epichlorohydrin was added, reacted in a microwave reactor at 85°C and 400 r / min for 7 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed 4 times with ethanol, and then washed 4 times with pure water, and vacuum dried at 65°C for 7 h to obtain quaternary ammonium-modified polyacrylonitrile;
[0073] (6) Dissolve hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile, and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution, 10 wt% quaternary ammonium modified polyacrylonitrile spinning solution, and 10 wt% polyacrylonitrile spinning solution, respectively; ultrasonically disperse modified nano manganese dioxide in anhydrous ethanol to prepare 2 wt% modified nano manganese dioxide dispersion; inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a propulsion speed of 0.7 ml / h, a voltage of 26 kV, and a distance between the needle tip and the collecting drum of 20 cm; The collecting drum was covered with a 400-mesh metal wire mesh, and the spinning was carried out at 25°C, 50% RH for 40 min. The spinning solution was replaced with quaternary ammonium modified polyacrylonitrile spinning solution, the propulsion speed was 0.6 ml / h, the voltage was 23 kV, and the spinning was carried out for 20 min. The spinning solution was replaced with polyacrylonitrile spinning solution, the propulsion speed was 0.5 ml / h, and the voltage was 16 kV. An atomizer containing modified nano-manganese dioxide dispersion was placed on the collecting drum with the spray direction of the atomizer being orthogonal to the collecting drum. The spinning was carried out for 20 min, and the air filter material was vacuum dried at 55°C for 7 h and peeled off from the collecting drum to obtain an air filter material.
[0074] Comparative Example 3
[0075] A method for preparing an air filter material, the method comprising the following steps:
[0076] (1) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:20, reacted at 70°C and 250 r / min for 2.5 h, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 55°C for 8 h to obtain carboxyl-modified polyacrylonitrile;
[0077] (2) Carboxyl modified polyacrylonitrile, glycidol and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.45:25, reacted in a microwave reactor at 75°C and 350 r / min for 1.5 h, ethylenediaminetetramethylenephosphonic acid in an amount equal to that of glycidol was added, reacted in a microwave reactor at 75°C and 350 r / min for 2 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 4 times, then washed with pure water 4 times, and vacuum dried at 65°C for 9 h to obtain hydrophilic modified polyacrylonitrile;
[0078] (3) Carboxyl-modified polyacrylonitrile, epichlorohydrin and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.55:30, reacted in a microwave reactor at 75°C and 400 r / min for 1 h, nitrogen was introduced, octadecyl dimethyl tertiary amine of the same mass as epichlorohydrin was added, potassium iodide of 0.02 times the mass of epichlorohydrin was added, reacted in a microwave reactor at 85°C and 400 r / min for 7 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 4 times, then washed with pure water 4 times, and vacuum dried at 65°C for 7 h to obtain quaternary ammonium-modified polyacrylonitrile;
[0079] (4) Dissolve hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution, 10 wt% quaternary ammonium modified polyacrylonitrile spinning solution and 10 wt% polyacrylonitrile spinning solution respectively. Inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a speed of 0.7 ml / h and a voltage of 26 kV. The distance between the needle tip and the collecting drum is 20 cm. Cover the collecting drum with a 400 mesh metal screen. Spin for 40 min at 25°C and 50% RH. Replace with quaternary ammonium modified polyacrylonitrile spinning solution at a speed of 0.6 ml / h and a voltage of 23 kV. Spin for 20 min. Replace with polyacrylonitrile spinning solution at a speed of 0.5 ml / h and a voltage of 16 kV. Spin for 20 min. Dry under vacuum at 55°C for 7 h. Peel off from the collecting drum to obtain an air filter material.
[0080] Comparative Example 4
[0081] A method for preparing an air filter material, the method comprising the following steps:
[0082] (1) 3-Chloropropylmethyldimethoxysilane, hexadecyldimethyl tertiary amine, sodium iodide and anhydrous ethanol were mixed uniformly in a molar ratio of 1.1:1:0.01:21, stirred and refluxed at 80°C and 400 r / min for 40 h under a nitrogen atmosphere, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure, washed with ethanol for 4 times, and vacuum dried at 55°C for 7 h to obtain an organosilicon quaternary ammonium salt;
[0083] (2) Mix nano manganese dioxide and anhydrous ethanol in a mass ratio of 1:42, disperse them uniformly under ultrasonication at room temperature for 25 min, stir them at 350 r / min for 2.5 h, add organosilicon quaternary ammonium salt twice the mass of nano manganese dioxide, reflux at 85°C and 350 r / min for 17 h, centrifuge at 9000 r / min for 10 min after the reaction is completed, wash them with ethanol for 5 times, and vacuum dry them at 55°C for 7 h to obtain modified nano manganese dioxide;
[0084] (3) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:20, reacted at 70°C and 250 r / min for 2.5 h, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 55°C for 8 h to obtain carboxyl-modified polyacrylonitrile;
[0085] (4) Carboxyl modified polyacrylonitrile, glycidol and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.45:25, reacted in a microwave reactor at 75°C and 350 r / min for 1.5 h, ethylenediaminetetramethylenephosphonic acid in an amount equal to that of glycidol was added, reacted in a microwave reactor at 75°C and 350 r / min for 2 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 4 times, then washed with pure water 4 times, and vacuum dried at 65°C for 9 h to obtain hydrophilic modified polyacrylonitrile;
[0086] (5) Carboxyl-modified polyacrylonitrile, epichlorohydrin, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.55:30, reacted in a microwave reactor at 75°C and 400 r / min for 1 h, nitrogen was introduced, octadecyl dimethyl tertiary amine of the same mass as epichlorohydrin was added, potassium iodide of 0.02 times the mass of epichlorohydrin was added, reacted in a microwave reactor at 85°C and 400 r / min for 7 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed 4 times with ethanol, and then washed 4 times with pure water, and vacuum dried at 65°C for 7 h to obtain quaternary ammonium-modified polyacrylonitrile;
[0087] (6) Dissolve hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile, and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution, 10 wt% quaternary ammonium modified polyacrylonitrile spinning solution, and 10 wt% polyacrylonitrile spinning solution, ultrasonically disperse modified nano manganese dioxide in anhydrous ethanol to prepare 2 wt% modified nano manganese dioxide dispersion, inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a propulsion speed of 0.7 ml / h and a voltage of 26 kV. The needle tip is aligned with the collecting roller. The distance was 20 cm, at 25°C, 50% RH, spinning for 40 min, changing to quaternary ammonium modified polyacrylonitrile spinning solution, the propulsion speed was 0.6 ml / h, the voltage was 23 kV, spinning for 20 min, changing to polyacrylonitrile spinning solution, the propulsion speed was 0.5 ml / h, the voltage was 16 kV, the atomizer filled with modified nano manganese dioxide dispersion was placed on the collecting drum, the atomizer spray direction was orthogonal to the collecting drum, spinning for 20 min, vacuum drying at 55°C for 7 h, peeling off from the collecting drum, and obtaining the air filter material.
[0088] In subsequent tests, the side close to the wire mesh is called the front side and serves as the airflow inflow side, and the side away from the wire mesh is called the back side and serves as the airflow outflow side.
[0089] Test Example 1
[0090] Filtration performance test: The prepared air filter material was tested using an automatic filter material tester with model TSI 8130A. The test conditions were room temperature, relative humidity of 50±4%, wind speed of 33.3 L / min, and the tested particles were sodium chloride with a mass particle size of 0.26 μm. The test sample size was 15 cm×15 cm. Each group of air filter materials prepared in the embodiments and comparative examples was tested three times and the average value was taken to record the filtration efficiency and pressure drop data.
[0091] The results are shown in Table 1.
[0092] Table 1
[0093]
[0094] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the air filter material prepared by the present invention has good air filtration efficiency and low pressure drop.
[0095] By comparison, the filtration efficiency of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that the quaternary ammonium group brought by the quaternary ammonium-modified polyacrylonitrile improves the filtration efficiency of the air filter material, and the positive charge carried thereon plays a role of electrostatic adsorption.
[0096] By comparison, the filtration efficiency of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that the ethylenediaminetetramethylenephosphonic acid on the hydrophilic modified polyacrylonitrile improves the filtration efficiency of the air filter material, and the negative charge carried thereon plays a role of electrostatic adsorption.
[0097] By comparison, the filtration efficiency and pressure drop of Examples 1 to 3 are greater than those of Comparative Example 3, indicating that the nano-manganese dioxide loaded by the nano-spray technology reduces the pore size of the third layer of spinning, increases the pressure drop, and improves the filtration efficiency.
[0098] By comparison, the filtration efficiency of Examples 1 to 3 is greater than that of Comparative Example 4, and the pressure drop of Examples 1 to 3 is less than that of Comparative Example 4, indicating that the positive ordered structure obtained by using the metal wire mesh brings smaller pore size and tighter structure, while also reducing the pressure drop.
[0099] Test Example 2
[0100] Antibacterial performance test: Using the agar plate diffusion method in GB / T 20944, the air filter material was cut into a circle with a diameter of 25mm, and the antibacterial performance of the air filter material was evaluated by using Escherichia coli and Staphylococcus aureus. The antibacterial effect of the air filter material was evaluated by measuring the size of its inhibition zone. Using the oscillation method in GB / T 20944, the air filter material was cut into 0.75±0.05g samples and mixed with the bacterial solution for 5 minutes. The oscillated bacterial solution was taken to agar culture medium for culture, and the antibacterial rate of the air filter material against Escherichia coli and Staphylococcus aureus was determined by the number of growing colonies, and the data was recorded.
[0101] The results are shown in Table 2.
[0102] Table 2
[0103]
[0104] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the air filter material prepared by the present invention has good antibacterial properties.
[0105] By comparison, the antibacterial circle diameter and the antibacterial rate of Examples 1 to 3 are greater than the antibacterial circle diameter and the antibacterial rate of Comparative Example 1, indicating that the quaternary ammonium group on the quaternary ammonium-modified polyacrylonitrile provides a good antibacterial effect, so that the prepared air filter material has an antibacterial effect.
[0106] By comparison, the antibacterial circle diameter and the antibacterial rate of Examples 1 to 3 are greater than the antibacterial circle diameter and the antibacterial rate of Comparative Example 3, indicating that the quaternary ammonium group grafted on the surface of the modified nano-manganese dioxide also provides a certain antibacterial effect, so that the prepared air filter material has a better antibacterial effect.
[0107] Test Example 3
[0108] Flame retardant performance test: According to GB / T 2406.1-2008, the limiting oxygen index of the air filter material is tested with an oxygen index instrument. The sample size is 150mm×10mm×3mm, and the data is recorded.
[0109] The results are shown in Table 3.
[0110] Table 3
[0111]
[0112] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the air filter material prepared by the present invention has good flame retardant properties.
[0113] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that the ethylenediaminetetramethylenephosphonic acid grafted on the surface of the hydrophilic modified polyacrylonitrile imparts a flame retardant effect to the air filter material, making it difficult to burn.
[0114] Test Example 4
[0115] Mechanical properties test: Test the breaking strength and breaking elongation of the prepared air filter material according to GB / T 24218.3-2010, and record the data.
[0116] The results are shown in Table 4.
[0117] Table 4
[0118]
[0119] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the air filter material prepared by the present invention has a breaking strength and a breaking elongation.
[0120] By comparison, the breaking strength and breaking elongation of Examples 1 to 3 are greater than those of Comparative Examples 1 and 2, indicating that the ethylenediaminetetramethylenephosphonic acid on the hydrophilic modified polyacrylonitrile and the quaternary ammonium group on the quaternary ammonium modified polyacrylonitrile undergo electrostatic bonding, thereby improving the mechanical properties of the air filter material.
[0121] By comparison, the breaking strength and breaking elongation of Examples 1 to 3 are greater than the breaking strength and breaking elongation of Comparative Example 4, indicating that the positive ordered structure brought by the use of the metal wire mesh also improves the breaking strength of the air filter material, and the ordered structure has better breaking strength than the disordered structure.
[0122] Test Example 5
[0123] Formaldehyde removal test: refer to the test method of GB / T 23761-2020. Except not using light source, other test conditions are the same. Formaldehyde is used as the gas to be passed in. The formaldehyde removal rate is tested and the data is recorded.
[0124] The results are shown in Table 5.
[0125] Table 5
[0126]
[0127] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 5, it can be found that the air filter material prepared by the present invention has a good formaldehyde removal effect.
[0128] By comparison, the formaldehyde removal rates of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that the modified nano-manganese dioxide loaded by nano-atomization on the air filter material has the effect of catalyzing the oxidation of formaldehyde, while the air filter material without the loaded modified nano-manganese dioxide has only the adsorption effect.
[0129] Test Example 6
[0130] Contact angle test: The prepared air filter material was cut into 1cm×2cm size, flattened with a tabletting mold to make the surface flat and uniform, and the contact angle between the front and back of the air filter material and water was tested with a water contact angle tester. The test method was to drop 5μL of water drops on the front and back of the air filter material at standard atmospheric pressure and 20°C, and measure the contact angle after the droplet stayed for 30s, and record the data.
[0131] The results are shown in Table 6.
[0132] Table 6
[0133]
[0134] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 6, it can be found that the air filter material prepared by the present invention has good hydrophilic wettability on the front side and super hydrophobicity on the back side.
[0135] By comparison, the front contact angles of Examples 1 to 3 are smaller than that of Comparative Example 2, indicating that the ethylenediaminetetramethylenephosphine grafted onto the surface of hydrophilically modified polyacrylonitrile enables the front side to obtain a super-hydrophilic structure with good wettability, which can better adsorb water molecules and absorb water molecules from the reverse hydrophobic layer by capillary action.
[0136] By comparison, the back contact angles of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that the modified nano-manganese dioxide loaded by the nano-atomization technology enables the back surface to obtain a super-hydrophobic structure. The super-hydrophobic surface has good anti-pollution performance and self-cleaning potential. At the same time, water molecules are difficult to remain on this surface, and a small amount of adsorbed water molecules are also transmitted to the front hydrophilic layer through capillary action, thereby keeping the back hydrophobic layer dry.
[0137] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An air filter material, characterized in that: The air filter material is prepared by first reacting organosilicon quaternary ammonium salt with nano manganese dioxide to obtain modified nano manganese dioxide; reacting polyacrylonitrile with sodium hydroxide solution to obtain carboxyl modified polyacrylonitrile; reacting carboxyl modified polyacrylonitrile with glycidol and ethylenediaminetetramethylenephosphonic acid to obtain hydrophilic modified polyacrylonitrile; reacting carboxyl modified polyacrylonitrile with epichlorohydrin and octadecyl dimethyl tertiary amine to obtain quaternary ammonium modified polyacrylonitrile; The hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile and polyacrylonitrile are prepared into a spinning solution and electrospun, and the last layer is loaded with modified nano manganese dioxide to obtain an air filter material; The organosilicon quaternary ammonium salt is prepared by reacting 3-chloropropylmethyldimethoxysilane with hexadecyldimethyl tertiary amine; The electrospinning process is to first spin with a hydrophilic modified polyacrylonitrile spinning solution, then spin with a quaternary ammonium modified polyacrylonitrile spinning solution, and finally spin with a polyacrylonitrile spinning solution; The loading of the modified nano manganese dioxide is carried out by using nano atomization technology.
2. An air filter material according to claim 1, characterized in that: The weight average molecular weight of the polyacrylonitrile is 149,000-150,000.
3. A method for preparing an air filter material, characterized in that: The method comprises the following preparation steps: (1) 3-chloropropylmethyldimethoxysilane, hexadecyldimethyl tertiary amine, sodium iodide and anhydrous ethanol were mixed uniformly in a molar ratio of 1.1:1:0.01:21, stirred and refluxed at 80-85°C and 300-500 r / min for 38-42 hours under a nitrogen atmosphere, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure, washed with ethanol for 3-5 times, and vacuum dried at 50-60°C for 6-8 hours to obtain an organosilicon quaternary ammonium salt; (2) Mix nano manganese dioxide and anhydrous ethanol in a mass ratio of 1:(40-45), disperse them evenly under ultrasonication at room temperature for 20-30 min, stir them at 300-400 r / min for 2-3 h, add quaternary ammonium salt of organosilicon twice the mass of nano manganese dioxide, reflux at 80-85°C and 300-400 r / min for 16-18 h, centrifuge at 8000-10000 r / min for 10-15 min after the reaction is completed, wash them with ethanol for 4-6 times, and vacuum dry them at 50-60°C for 6-8 h to obtain modified nano manganese dioxide; (3) Polyacrylonitrile and 10 wt% sodium hydroxide solution were mixed uniformly in a mass ratio of 1:(15-25), reacted at 65-75°C and 200-300 r / min for 2-3 hours, naturally cooled to room temperature, filtered, washed alternately with ethanol and pure water until neutral, and vacuum dried at 50-60°C for 7-8 hours to obtain carboxyl-modified polyacrylonitrile; (4) Carboxyl modified polyacrylonitrile, glycidol and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(0.4-0.5):(20-30), reacted in a microwave reactor at 70-75°C and 300-400 r / min for 1.5-2 h, added ethylenediaminetetramethylenephosphonic acid in an amount equal to that of glycidol, reacted in a microwave reactor at 70-75°C and 300-400 r / min for 2-2.5 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 3-5 times, then washed with pure water 3-5 times, and vacuum dried at 60-70°C for 8-10 h to obtain hydrophilic modified polyacrylonitrile; (5) Carboxyl modified polyacrylonitrile, epichlorohydrin and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(0.5-0.6):(25-35), reacted in a microwave reactor at 70-75°C and 300-500 r / min for 1-1.5 h, nitrogen was introduced, octadecyl dimethyl tertiary amine of the same mass as epichlorohydrin was added, potassium iodide of 0.02 times the mass of epichlorohydrin was added, reacted in a microwave reactor at 80-85°C and 350-450 r / min for 6-8 h, cooled naturally to room temperature, ultrafiltered with a hollow fiber membrane with a pore size of 1000 Da, washed with ethanol 3-5 times, then washed with pure water 3-5 times, and vacuum dried at 60-70°C for 8-10 h to obtain quaternary ammonium modified polyacrylonitrile; (6) Dissolve hydrophilic modified polyacrylonitrile, quaternary ammonium modified polyacrylonitrile, and polyacrylonitrile in N,N-dimethylformamide to prepare 10 wt% hydrophilic modified polyacrylonitrile spinning solution, 10 wt% quaternary ammonium modified polyacrylonitrile spinning solution, and 10 wt% polyacrylonitrile spinning solution, respectively; ultrasonically disperse modified nano manganese dioxide in anhydrous ethanol to prepare 2 wt% modified nano manganese dioxide dispersion; inject the hydrophilic modified polyacrylonitrile spinning solution into a syringe at a propulsion speed of 0.7 ml / h, a voltage of 25-27 kV, a distance between the needle tip and the collecting drum of 20 cm, and cover the collecting drum with 400 mesh The metal mesh was spun at 23-27°C and 46%-54%RH for 38-44min, then replaced with quaternary ammonium modified polyacrylonitrile spinning solution at a propulsion speed of 0.6ml / h and a voltage of 22-25kV for 19-22min, then replaced with polyacrylonitrile spinning solution at a propulsion speed of 0.5ml / h and a voltage of 15-18kV. An atomizer containing modified nano-manganese dioxide dispersion was placed on the collecting drum with the spray direction of the atomizer being orthogonal to the collecting drum. The material was spun for 19-22min, dried in vacuum at 50-60°C for 6-8h, and peeled off from the collecting drum to obtain an air filter material.
4. The method for preparing an air filter material according to claim 3, characterized in that: The reaction process of the organosilicon quaternary ammonium salt in step (1) is as follows: 。 5. The method for preparing an air filter material according to claim 3, characterized in that: The reaction process of carboxyl-modified polyacrylonitrile in step (3) is as follows: 。 6. The method for preparing an air filter material according to claim 3, characterized in that: The hydrophilic modified polyacrylonitrile reaction process in step (4) is as follows: ; 。 7. The method for preparing an air filter material according to claim 3, characterized in that: The reaction process of quaternary ammonium modified polyacrylonitrile in step (5) is as follows: ; 。